2021
DOI: 10.3390/bs11050063
|View full text |Cite
|
Sign up to set email alerts
|

Mass Media Exposure and Safer Sex Negotiation among Women in Sexual Unions in Sub-Saharan Africa: Analysis of Demographic and Health Survey Data

Abstract: (1) Background: Improving sexual autonomy among women in sexual unions comes with various benefits, including the reduction of sexually transmitted and blood-borne infections. We examined the relationship between mass media exposure and safer sex negotiation among women in sub-Saharan Africa (SSA). (2) Methods: The study involved a cross-sectional analysis of Demographic and Health Survey (DHS) data of 29 sub-Saharan African countries. A total of 224,647 women aged 15–49 were included in our analyses. We exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 30 publications
(51 reference statements)
5
11
0
Order By: Relevance
“…Similar to our findings, the studies conducted in lower and middle-income countries of Sub-Saharan Africa and India identified that media exposure is highly associated with a higher level of women's empowerment [24][25][26]. The evidence shows women's exposure to mass PLOS GLOBAL PUBLIC HEALTH PLOS GLOBAL PUBLIC HEALTH media improves access to information which empowers them to take part in the decision-making process by changing social norms, behaviours, and practices [26]. The media positively influence a person's will, assets, knowledge, and power relation within the family and society to make them more independent in their action [27].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to our findings, the studies conducted in lower and middle-income countries of Sub-Saharan Africa and India identified that media exposure is highly associated with a higher level of women's empowerment [24][25][26]. The evidence shows women's exposure to mass PLOS GLOBAL PUBLIC HEALTH PLOS GLOBAL PUBLIC HEALTH media improves access to information which empowers them to take part in the decision-making process by changing social norms, behaviours, and practices [26]. The media positively influence a person's will, assets, knowledge, and power relation within the family and society to make them more independent in their action [27].…”
Section: Discussionsupporting
confidence: 91%
“…However the basic education of women, husband's education, religion, size of household, and place of residence in terms of urban vs rural do not have any significant association with women's autonomy. Similar to our findings, the studies conducted in lower and middle-income countries of Sub-Saharan Africa and India identified that media exposure is highly associated with a higher level of women's empowerment [24][25][26]. The evidence shows women's exposure to mass PLOS GLOBAL PUBLIC HEALTH PLOS GLOBAL PUBLIC HEALTH media improves access to information which empowers them to take part in the decision-making process by changing social norms, behaviours, and practices [26].…”
Section: Discussionsupporting
confidence: 87%
“…Two, women’s individual characteristics are important factors that either deter or enhance sexual autonomy. As shown in the study, and in line with findings in existing studies, individual characteristics such as maternal education [ 26 , 42 ], media exposure [ 40 , 43 ], nature of first marriage [ 7 , 40 ], and employment [ 40 ] play significant roles as levers of sexual and reproductive autonomy. This finding gives credence to many existing strategies on improving women’s characteristics particularly women’s education and economic status.…”
Section: Discussionsupporting
confidence: 81%
“…This result suggests that the Ghanaian government should deploy the media to spread awareness of poor sanitation and hygiene behaviours, such as open defecation. This may raise rural women's knowledge of the harmful health implications of open defecation and the need to stop engaging in this hazardous behaviour [46].…”
Section: Discussionmentioning
confidence: 99%